Giant uterine leiomyoma: a case report with literature review - Kalyan, Sonali; Sharma, Sonam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Uterine leiomyomas are one of the most common entities encountered in routine gynaecological practice; however, the giant uterine myomas are very rare and can often create a diagnostic dilemma and therapeutic challenge owing to their size, non-specific clinical presentation and degenerations. Here, in this article we review the literature on giant uterine leiomyomas and report one such case in a 38-year-old woman who presented with the complaints of vague abdominal lump, enlargement of abdomen, dysmenorrhea, lower abdominal and pelvic pain since last 2 years and a 6-month history of increased frequency of micturation. Physical examination and radiological investigations suggested a giant abdominopelvic mass, probably a uterine or an ovarian malignancy. An exploratory laparotomy was performed followed by total hysterectomy. Grossly, the specimen was a 15.2 kg uterine leiomyoma measuring 18x18x13 cm in size. Histologically, the benign leiomyoma showed cystic degeneration. The patient’s post-operative and follow-up period was uneventful.